2012
DOI: 10.1002/ccd.23144
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐term outcomes of carotid artery stenting in patients with angiographic string sign

Abstract: We suggest that CAS might be performed with acceptable procedural risk in patients presenting with SS, which is unsuitable for surgery. However, patients' clinical and angiographic characteristics must be carefully evaluated when considering interventional therapy, regardless of the favorable procedural outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…Apart from operator training, it is equally essential to carefully select patients in order to reach favourable outcomes [18]. …”
Section: Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from operator training, it is equally essential to carefully select patients in order to reach favourable outcomes [18]. …”
Section: Patient Selectionmentioning
confidence: 99%
“…One must also be very reserved in indicating patients with multiple clinical high risk factors, which might influence the patient's long-term prognosis per se despite favourable procedural outcomes [18, 30]. In such case, the benefit of CAS over medical treatment must be critically evaluated, especially in asymptomatic patients.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Reported outcomes were highly heterogeneous and ranged from a 30-day stroke/death risk of 0–11.1% for CEA [1113, 20] to 0–9.2% for CAS [57, 1618] and 0–43% for best medical treatment (BMT) [8, 12, 19]. Furthermore, analyses of published studies are hampered by both a variety in inclusion criteria and the reporting of different clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In a consecutive series of 25 patients with angiographic string sign, Nikas et al [16] reported a 100% technical success rate and no periprocedural adverse clinical events. Spacek et al [15] reported equally impressive results in a series of 19 patients, including 95% technical success and 0% incidence of periprocedural stroke or death. Post hoc analysis revealed that approximately 7% of patients in our series had a string sign; however, the presence of a string sign was not a predictor of periprocedural complications.…”
Section: Discussionmentioning
confidence: 87%